PART I: OPTIMIZATION OF HYDRALAZINE HYDROCHLORIDE IMMEDIATE RELEASE LAYER IN ANTIHYPERTENSIVE BILAYER TABLET - TRIVEDI, HARSH; PATEL, KUNAL; OZA, NISHANT A.; SAGAR, SWATI (International Journal of Applied Pharmaceutics, 2020)
Objective: Aim of the present study was the optimization of the immediate release (IR) layer containing hydralazine hydrochloride (HHC) 25 mg and compressed with a sustained-release (SR) layer of isosorbide dinitrate (ISDN) 40 mg to decrease the dosing frequency. Methods: In this study, Drug-excipients compatibility study was carried out by FT-IR and a preliminary trial was conducted for screening of super disintegrating agents. The amount of sodium starch glycolate (SSG) (X1) and the amount of ac-di-sol® (X2) was chosen as independent variables in 32 full factorial design while wetting time (WT) (Y1), disintegration time (DT) (Y2) and In vitro drug release at 15 min (Q15) (Y3) were taken as dependent variables. Multiple linear regression analysis, ANOVA, and graphical representation of the influence of factor by 3D plots were performed by using sigma plot 13.0. In the present study, the following constraints were used for the selection of an optimized batch: WT<16 s, DT<25 s, and Q15>90%. To validate the evolved mathematical models, a checkpoint batch was selected from its desirability value. Results: FT-IR spectra show that the drug and excipients were compatible with each other. The calculated F values found for WT, DT, and Q15 were 045.559, 077.100 and 278.760, respectively. All Calculated F values are greater than tabulated values for all dependent variables. Prepared checkpoint was selected from its desirability value 0.935 and it gives a 100% drug release within 30 min. Conclusion: These results confirm that the prepared HHC 25 mg IR layer is used for rapid control of hypertension.